21st Century Skills: What Are They and How Do We Assess Them?. Issue 4 (1st October 2016) - Geisinger, Kurt F.
ABSTRACT: One of the "hottest" topics in the educational measurement community in the past decade has been the assessment of 21st century skills. This special issue demonstrates work being performed in this realm. The present article provides a context for the four primary articles that follow and a brief but broad view of some models of 21st century skills. The articles that follow are active projects developing assessments that focus on the changing cognitive skills required for this new century. It is clear that education that has emphasized memory and routine problem solving needs a metamorphosis and the measures described in this issue portend a brave new educational world.